Tunicamycin promotes metastasis through upregulating endoplasmic reticulum stress induced GRP78 expression in thyroid carcinoma - Guohong Zhao (Cell & Bioscience, 2020)
Abstract Background Thyroid cancer (TC) is the most common type of endocrine malignancy and its incidence is increasing over years. Conventional surgery, radiotherapy and chemotherapy are difficult to improve the significant effects of it due to aggression and metastasis of poorly differentiated thyroid cancer (PDTC) and anaplastic thyroid cancer (ATC), and these are regarded as the most malignant types of TC. Glucose-regulated protein (GRP78) is the key molecule of tumor growth, apoptosis and metastasis. However, the underlying mechanisms of GRP78 in TC still require discussion. This study aimed to explore the role of GRP78 and its potential mechanism in TC. Results GRP78 expression was increased in TC tissues when compared with adjacent normal tissues. Besides, down-regulation of GRP78 significantly inhibited the metastatic and proliferative ability of ATC cells in in vitro studies. In addition, tunicamycin-induced ER stress up-regulated the expression of GRP78, PERK and XBP1 as well as reversed the metastatic ability of GRP78 in ATC cells. Bioinformatics and statistical analysis of gene ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways for RNA-sequencing data with regard to si-GRP78 and si-control showed that GRP78 might regulate the ability of metastasis through extracellular matrix (ECM) remodeling in ATC cells, as well as the expression of ECM components such as COL1A1 and MMP13, which were highly relevant to ATC cells. The analysis of GEPIA database confirmed that high genomic amplification of MMP13 and COL1A1 in TC tissues showed correlation with TNM stage. Further western blotting analysis showed that MMP13 might be the target of GRP78 in ATC cells and ER stress could activate the expression of MMP13 that is suppressed by GRP78 depletion. Conclusions GRP78 acts as an important regulator of metastasis under ER stress. In addition, the function of GRP78 might be mediated by ECM remodeling in ATC cells, implicating it as a therapeutic target in TC.